3-Year Follow-up of a Long-Term Registry-Based Multicentre Study on Vitamin E Diffused Polyethylene in Total Hip Replacement. Issue 1 (January 2016) - Sillesen, Nanna H.; Greene, Meridith E.; Nebergall, Audrey K.; Huddleston, James I.; Emerson, Roger; Gebuhr, Peter; Troelsen, Anders; Malchau, Henrik
Purpose: Preclinical studies of vitamin E diffused highly cross-linked polyethylene (E-XLPE) has shown enhanced mechanical properties with less wear. The purpose of our study was to document the early clinical outcome of E-XLPE to ensure, for the safety of patients, that there are no unforeseen early adverse events from using this new biomaterial. Methods: The enrolled patients (n = 977) have received either a porous titanium coated or porous plasma sprayed acetabular shell with either a E-XLPE liner or a medium cross-linked (AXL) liner. At each follow-up 5 patient-reported outcome measures (PROMs) were completed: Harris Hip Score, Case Mix Indicator, UCLA Activity Score, SF-36, and EQ-5D. Radiographs were measured for cup and stem position, as well as femoral head penetration into the liner (wear). Postoperative complications and revisions were collected. Results: At 3 years follow-up, there were 13 revisions due to: 4 periprosthetic fractures; 1 sepsis; 6 instabilities; and 2 implant mismatches at surgery. Wear of the hip implant, calculated by software analysis of pelvis x-rays, from the postoperative interval to 3 years showed a liner penetration rate of 0.027 mm/year for AXL and 0.005 mm/year for E-XLPE with no significant difference between the 2 (p = 0.24). Improvement was seen in all PROMs from the preoperative interval to 3 years after surgery (p<0.0001). Conclusions: Early follow-up of the E-XLPE and AXL liners show low penetration. PROMs indicate improvement after total hip arthroplasty in functionality and quality of life across the centers. We have not observed any early in vivo adverse effects from diffusing the liners with vitamin E. Trial registration: ClinicalTrials.gov Identifier: NCT00545285.